Variation in narrative identity is associated with trajectories of mental health over several years. [article]. - Adler, Jonathan M.; Turner, Ariana F.; Brookshier, Kathryn M.; Monahan, Casey
This article presents 2 longitudinal studies designed to assess the relationship between variability in narrative identity and trajectories of mental health over several years. In Study 1, core scenes from 89 late-mid-life adults? life stories were assessed for several narrative themes. Participants? mental health and physical health were assessed concurrently with the narratives and annually for the subsequent 4 years. Concurrent analyses indicated that the themes of agency, redemption, and contamination were significantly associated with mental health. Longitudinal analyses indicated that these same 3 themes were significantly associated with participants? trajectories of mental health over course of 4 years. Exploratory analyses indicated that narratives of challenging experiences may be central to this pattern of results. In Study 2, similar longitudinal analyses were conducted on a sample of 27 late-mid-life adults who received a major physical illness diagnosis between the baseline assessment and 6 months later and a matched sample 27 control participants who remained healthy throughout the study. Participants? mental health and physical health were assessed every 6 months for 2 years. In this study, the themes of agency, communion, redemption, and contamination in participants? life narratives collected at baseline (before any participant became sick) were significantly associated with mental health in the group of participants who went on to receive a medical diagnosis, but not in the control group. Taken together, the results of these 2 studies indicate that the way an individual constructs personal narratives may impact his or her trajectory of mental health over time. - - (from the authors)